Effects of step lengths on biomechanical characteristics of lower extremity during split squat movement - Song, Qingquan; Ma, Mujia; Liu, Hui; Wei, Xiaobin; Chen, Xiaoping (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: To quantify the effects of increasing the step length of the split squat on changes in kinematics, kinetics, and muscle activation of the lower extremity.Methods: Twenty male college students participated in the test (age: 23.9 ± 3.7, height:175.1 ± 4.9). Data on kinematics, kinetics, and EMG were collected during split squat exercise at four different step lengths in a non-systematic manner. One-way repeated measurements ANOVA were used to compare characteristic variables of peak angle, moment, and RMS among the four step length conditions.The step length significantly changes the peak angles of the hip (p = 0.011), knee (p = 0.001), ankle (p < 0.001) joint, and the peak extension moment of the hip (p < 0.001), knee (p = 0.002) joint, but does not affect the ankle peak extension moment (p = 0.357) during a split squat. Moreover, a significant difference was observed in the EMG of gluteus maximus (p < 0.001), vastus medialis (p = 0.013), vastus lateralis (p = 0.020), biceps femoris (p = 0.003), Semitendinosus (p < 0.001), medialis gastrocnemius (p = 0.035) and lateralis gastrocnemius (p = 0.005) during four step lengths, but no difference in rectus femoris (p = 0.16).Increases in step length of split squat had a greater activation on the hip extensor muscles while having a limited impact on the knee extensor muscles. The ROM, joint moment, and muscle activation of the lead limb in the split squat all should be considered in cases of individual preventative or rehabilitative prescription of the exercise. Moreover, the optimal step length for strength training in healthy adults appears to be more suitable when it is equal to the length of the individual lower extremity.